The Ambiguity of Norms in Article 66 (C) of Law No. 30/1999 on Arbitration And Alternative Dispute Resolution: Causes, Implications And Resolutions - Muhamad Dzadit Taqwa; Tazkia Nafs Azzahra; Maria Jasmine Putri Subiyanto (Faculty of Law, Universitas Jenderal Soedirman, 2022)
According to Article 66 Letter C of Law Number 30/1999, one of the requirements for an international arbitral award to be accepted and executed in Indonesia is that it does not violate public order. There is an issue with the norms’ ambiguity; it concerns the definition and the application of the term